PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR LOMPAT TINGGI PADA SISWA KELAS V SDN 188 MANUNGGAL - Debora Panimba; Nur Afni; Erwin Nurdiansyah; Mulyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve high jump learning outcomes among fifth-grade students at SDN 188 Manunggal by implementing the Jigsaw cooperative learning model. The study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 31 fifth-grade students. Data were collected using performance tests, written tests, and classroom observations and were analyzed using descriptive quantitative and qualitative techniques. The findings indicated that the implementation of the Jigsaw cooperative learning model gradually improved students' learning outcomes. The mean score increased from 60 in the pre-cycle to 71 in Cycle I and 78 in Cycle II. Likewise, the learning mastery level improved from 39% in the pre-cycle to 71% in Cycle I and reached 81% in Cycle II, exceeding the predetermined success criterion. In addition to improving learning outcomes, the Jigsaw model enhanced students' active participation, collaboration, responsibility, and self-confidence throughout the learning process. Therefore, the Jigsaw cooperative learning model can be considered an effective instructional strategy for improving high jump learning outcomes in elementary school physical education.